A Study on Setting up a Database for Maternal Health Care Program in Darbandikhan-Kurdistan - Shakor, Jamal K.; Mohammed, Sabah Sh.; Hamakarim, Yadgar H.; Ahmed, Abbas M. (Journal of University of Human Development, 2016)
There are around 8.64 million women in Iraq who need to maternal health. While, maternal health program in Iraq is considerably down regulated, the vertical national health program, maternal health, has been not monitored appropriately. The aim of this study was to determine the most essential preliminary indicators for monitoring maternal health program in Kurdistan/ Iraq, and to assess those technical challenges for computerizing the maternal health program of Kurdistan Regional Government. This is interventional hospital based study which was carried out in Darbandikhan district- Kurdistan State. An access database was developed for entering whole records of the maternal health program components data in the 200 mothers’ file. And, we got staff belief about database. The study has shown that antenatal care visit record would be a good indicator for assessing maternal health program, when the program was computerized. And, the staff had a positive attitude to computerize the program. This database could accelerate the monitoring and evaluating the maternal health program in considering to indicators of the program.